Code-Switching among Teen Characters in the Film Eiffel… I’m in Love - Nuranaffi, Delia; Ardianto, Ardik (Journal of Language Intelligence and Culture, 2026)
This study looks at how the teenage characters in the Indonesian film Eiffel... I’m in Love (2003) switch between Indonesian, English, and French in their daily conversations. Code-switching is a well-known occurrence in bilingual communication, especially among young people who are constantly exposed to global media and multilingual settings. The research employed a descriptive qualitative method, analyzing and categorizing all instances of language switching found into each type of the three main types of code-switching, viz. inter-sentential, intra-sentential, and tag-switching. The findings revealed that Intra-sentential switching was the most predominant type of CS found in the dialogues, confirming how smoothly foreign words are incorporated into Indonesian sentences. The CSs served various distinct functions, including expressing emotions, adding emphasis, building social identity, and keeping conversations flowing naturally. The results further indicated that the code-switching was not randomly selected or arbitrary; rather, it reflected the characters’ relationships and the cultural milieu of Indonesian youth in the early 2000s. Multilingual dialogue in the film, as highlighted in this study, mirrors authentic bilingual behavior driven by the impact of youth identity within global culture.